Insetos-praga e inimigos naturais associados à macieira e pessegueiro - Costa, Marlice Botelho (2010)
Agricultural systems need adequate techniques to practice pest management, including including monitoring and identification of their natural enemies. Due to anthropization, agricultural landscapes become unprotected in terms of biodiversity. Thus, the use of plant strips associated with crops is capable of providing important resources for the conservation of natural enemies that act to control pest insects. In this context, the first stage of this research was conducted in apple trees at INRA, Montfavet, France. The objective was to compare the effect of vegetation strips with botanical species used in apple orchards and distance factor between strip and rows of cultivation on the occurrence of Cydia pomonella and natural enemies. It was found that the number of larvae of C. pomonella did not differ between the strips, however, it was lower in apple trees located in the planting rows near the vegetation strips. The highest number of parasitoids was in grass strip and the Carabidae in the wildflower strip. The second part of this research was conducted in an area planted with apple and peach trees at EPAMIG in Maria da Fé, Brazil. The objective was to know the population fluctuation of Grapholita molesta, fruit flies and Vespidae present in these orchards. Adults of G. molesta were collected with Delta traps and pheromone and the tephritid adults with “Pet” traps and hydrolyzed protein. Adults of G. molesta were observed during autumn and winter in peach and apple trees. Larvae of G. molesta were observed in the same period in peach and were not observed in apple. Tephritid adults were found in spring and summer, with 86% Anastrepha spp. and 14% Ceratitis capitata. Larvae of C. capitata in peach fruits occurred in October and Anastrepha in November, not being observed in apple. Wasps were collected in "Pet" and Moericke trap placed in these two cultures. In the apple tree were collected, 24 morpho-species belonging to 12 genus and in peach tree 21 morpho-species in nine genus. The most frequent were Agelaia multipicta and Agelaia vicina for the two fruit trees. The most abundant genus were Polybia and Polistes. Among the species, four are unpublished records for Minas Gerais, Angiopolybia sp.1, Ceramiopsis sp.1, Nectarinella sp.1, Pachodynerus sp.1. The greatest diversity, abundance and richness of wasps occurred in an apple orchard, compared to those in peach trees. Of the insects sampled, at least five genus are known as predators of pest insects and have as part of their food source, caterpillars that occur in cultivated or spontaneous plants.